Creative reconstructions : multilateralism and European varieties of capitalism after 1950 - Fioretos, Karl Orfeo, 1966- (Cornell studies in political economy., 2011)
'Creative Reconstructions' expands the reader's understanding of the historic relationship between varieties of capitalism and international cooperation.